Review: Hepatoprotector Compounds in Plant Extracts - DICHY NURYADIN ZAIN; Riezki Amalia; Jutti Levita (Universitas Padjadjaran, 2018)
Many plants have been reported to possess hepatoprotective activity. The mechanism has not yet been revealed, but it was predicted due to the antioxidants that could prevent the formation of free radicals produced by hepatotoxins. Of the 30 plants studied, Crocus sativus gave the largest hepatoprotector activity at a dose of 20 mg / kg, followed by Uncaria gambier Roxb. with a dose of 30 mg / kg and Melastoma malabathricum Leaf at a dose of 50 mg / kg. Keywords: Liver, CYP450, antioxidant, free radicals